CHARACTERIZATION OF WOOD PARTICLEBOARD WITH ADDITION OF LIGNOCELLULOSIC MATERIAL ALTERNATIVE IN MIDDLE LAYER - CAMPOS, Cristiane Inácio de; FERREIRA, Bruno S.; PRATES, Glaucia Aparecida; GOVEIA, Danielle (Revista Brasileira de Engenharia de Biossistemas, 2013)
This work is the production of particleboard of particles reconstituted from MDP (Medium Density Particleboard) adding particles in the inner layer of Mimosa Scarelli, popularly known as bracatinga, the ratios of 0%, 25%, 50%, 75% and 100%. The panel produced is composed of three layers, two external particles with smaller particle size and an inner layer composed of particles of larger particle sizes. Assays were performed based on physical and mechanical NBR 14.810/2006 for the determination of the board density, thickness swelling, water absorption, moisture content, bending strength, shear strength and residual moisture, and testing of particle size not existing in the standard cited. The results were analyzed and compared the results of the commercial boards made from 100% eucalyptus, based on the limits specified by the ABNT NBR 14.810/2006. The values of the tests were close to the normative specifications indicating positively the production of MDP with wood decay.